Adobe Fireworks CS6 - Babbage, Jim (Classroom in a book., 2012)
Those creative professionals seeking the fastest, easiest, most comprehensive way to learn Adobe Fireworks choose Adobe Fireworks CS6 Classroom in a Book from the Adobe Creative Team. The 14 project-based lessons in this book show readers step-by-step the key techniques for working in Fireworks. Readers will learn what they need to know to design and mock up Web pages or interfaces for rich Internet applications or tablet apps. In addition readers will learn how to demo a design for a client in real time, export the design as an interactive PDF, and export vector design elements as CSS3-only markup for use in websites. This edition, fully revised for CS6, covers CSS extraction using the CSS Properties panel, jQuery Mobile skinning, and sprite creation. It also includes instruction on working with the Styles panel and several new enhancements to the Properties panel, including the new color selection and gradient editing features. The companion DVD includes lesson files so readers can work along with the book. "The Classroom in a Book series is by far the best training material on the market. Everything you need to master the software is included: clear explanations of each lesson, step-by-step instructions, and the project files for the students." -Barbara Binder, Adobe Certified Instructor, Rocky Mountain Training Classroom in a Book(R), the best-selling series of hands-on software training workbooks, helps you learn the features of Adobe software quickly and easily. Classroom in a Book offers what no other book or training program does-an official training series from Adobe Systems Incorporated, developed with the support of Adobe product experts.the support of Adobe product experts.